(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
Elderly people are susceptible populace for violent crime or abuse and neglect. About 7% of India’s population are composed of elder persons and with improvements in socioeconomic conditions and increasing life expectancy, it is expected that this group may increase further. This increase of elder population has expanded a potential group of crime victims who are vulnerable to violence. The present case report summarizes two cases of elder homicides and addresses the issue. Some measures are also suggested to prevent the violence and death within this vulnerable population.